Uji Aktivitas Antihiperurisemia Dari Daun Hijau Tanaman Pucuk Merah (Syzygium myrtifolium Walp.) Terhadap Mencit Jantan (Mus musculus) - Juwita, Retno; Saleh, Chairul; Sitorus, Saibun (JURNAL ATOMIK, 2017)
Antihyperuricemia activity tests were conducted on an ethanol extract of green leaf plant red bud (Syzygium myrtifolium Walp.). Hyperuricemia is a condition in which uric acid levels in the blood increases due to the consumption of high purine is converted into uric acid. Antihyperuricemia activity test ethanol extract of green leaf plant red bud (Syzygium myrtifolium Walp.) Conducted on male white mice with a variety of doses of 1.85, 3.7 and 7.4 mg/kg. Extract dose of 7.4 mg/kg dose is the closest percentage drop on allopurinol which lowers blood uric acid levels at 55.04 %. Phytochemical screening showed that the green leaf plant red bud contains alkaloids, triterpenoids, steroids, phenolics, flavonoids and saponins. These results indicate that the ethanol extract of green leaf plant red bud has antihyperuricemia activity.